An efficient Fe(III)-catalyzed 1, 6-conjugate addition of para-quinone methides with fluorinated silyl enol ethers toward β, β-diaryl α-fluorinated ketones. Issue 52 (27th December 2018) - Hao, Yong-Jia; Hu, Xiao-Si; Yu, Jin-Sheng; Zhou, Feng; Zhou, Ying; Zhou, Jian
Abstract: Reported here is a highly efficient 1, 6-conjugate addition of fluorinated silyl enol ethers to para -quinone methides, allowing facile access to a range of β, β-diaryl α-fluorinated ketones with good to high yields. Fe(OTf)3 was identified as the optimal catalyst, with the loading of 3 mol%. Notably, this represent the first 1, 6-conjugate addition with fluorinated silyl enol ethers. The synthetic potential of the resulting adducts is also demonstrated. Graphical abstract: